EDUKASI BERKELOMPOK UNTUK PENINGKATAN KEPATUHAN TERAPI PADA ODHIV DI WILAYAH KERJA PUSKESMAS RAWASARI KOTA JAMBI - Kusdiyah, Erny; Darmawan, Armaidi; Aurora, Wahyu Indah Dewi; Harahap, Huntari; Syauqy, Ahmad; Nuriyah, Nuriyah (Universitas Jambi, 2024)
HIV/AIDS infection (ODHIV) remains a significant public health issue in Indonesia. One of the main challenges in managing HIV/AIDS is adherence to antiretroviral (ARV) therapy among ODHIV. Low adherence can lead to drug resistance, decreased quality of life, and increased risk of virus transmission. Factors influencing ARV adherence include stigma, discrimination, and the knowledge of ODHIV about the therapy. Education was conducted through group counseling, starting with a pre-test to assess participants' knowledge about HIV treatment. After the pre-test, a counseling session on